2011
DOI: 10.1097/inf.0b013e31821038d9
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of the Heptavalent Pneumococcal Conjugate Vaccine on the Epidemiology of Acute Otitis Media Complicated by Otorrhea

Abstract: After the introduction of immunization, otorrhea incidents decreased considerably, mainly because of the decrease in pneumococcal disease. H. influenzae is now the predominant organism. Serotype 19A has increased significantly and is the most common nonvaccine pneumococcal serotype. Penicillin resistance has increased in recent years.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
51
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(52 citation statements)
references
References 35 publications
1
51
0
Order By: Relevance
“…To our knowledge, this is the first meta-analysis of randomized clinical trials to assess the safety and immunogenicity of the 13-valent pneumococcal conjugate vaccine versus the 7-valent pneumococcal conjugate vaccine in infants. Previous studies [34][35][36] have evaluated another conjugate vaccine (7, 9, 11-valent) and recorded outcomes of IPD, otitis, or pneumonia [37][38][39]. Other reviews compared different 13-valent pneumococcal conjugate vaccine schedules in infants [40,41], or were not systematic reviews [10,42,43].…”
Section: Discussionmentioning
confidence: 96%
“…To our knowledge, this is the first meta-analysis of randomized clinical trials to assess the safety and immunogenicity of the 13-valent pneumococcal conjugate vaccine versus the 7-valent pneumococcal conjugate vaccine in infants. Previous studies [34][35][36] have evaluated another conjugate vaccine (7, 9, 11-valent) and recorded outcomes of IPD, otitis, or pneumonia [37][38][39]. Other reviews compared different 13-valent pneumococcal conjugate vaccine schedules in infants [40,41], or were not systematic reviews [10,42,43].…”
Section: Discussionmentioning
confidence: 96%
“…are mainly based on aspirates of MEF from Sweden, Finland, Canada, Colombia, Greece, and the USA [7,31]. Furthermore, also due to restriction on tympanocentesis, only limited data were available from the German National Reference Center for Streptococci (GNRCS) from the time prior to the introduction of the pneumococcal conjugate vaccination in Germany [32].…”
Section: Discussionmentioning
confidence: 99%
“…Results of previous AOM studies consistently revealed S. pneumoniae, Haemophilus influenzae, Moraxella catarrhalis, and Streptococcus pyogenes as major bacterial pathogens in the development of AOM [7,31].…”
Section: Introductionmentioning
confidence: 93%
“…3,7 In the case of AOM, similar serotype replacement by serotype 19A has been reported. [14][15][16][17] The serotype that follows next in prevalence after serotype 19A has varied in past reports. Casey et al 14 study showed that serotype 19A was the most frequent serotype and serotype 15A came next.…”
Section: Discussionmentioning
confidence: 97%